Rule and identity in a diverse Mediterranean society: aspects of the county of Tripoli during the twelfth century - Lewis, KJ (2014)
The county of Tripoli (Lebanon) was one of four “crusader states” established in the Levant after the First Crusade (1095-99). Compared to the other states, the county of Tripoli has suffered from a disproportionate level of historiographical neglect. What has been produced has taken an institutional and Eurocentric approach to the subject and its sources. The present thesis jettisons this in favour of a post-institutional methodology, approaching the county from the perspectives of geography and demographics, which together ensure that it is treated within its proper Syro-Lebanese context. Chapter one looks at the role of local geography in shaping the political frontiers of the county of Tripoli and its neighbours, arguing that topography was more important than the agency of the European settlers. Chapter two continues to challenge traditional assumptions regarding European influence, arguing that the specifically southern French origins of many of the county’s settlers were of little significance. Chapter three analyses the use of Arabic by the Frankish government of the county, informed by an awareness of diglossia. It argues that the Franks were more likely to know spoken Arabic than written, but remained reliant upon local intermediaries when ruling over Arabophones. Chapter four looks at popular religion, arguing that the cross-fertilisation of religious beliefs and practices was widespread but poorly understood by the contemporary intelligentsia, upon whose sources historians rely. As a whole, the thesis argues that the county’s inhabitants lacked a distinctive culture, identity, religion or language. The sole justification for viewing the county as an integrated unit is geographical.